Analysis of cardiac surgeries and operative mortality at the National Cardiovascular Institute during 2022 - Polo-Gutierrez, Gerber (2023)
Objective. To describe cardiac surgeries, their approaches, and determine operative mortality according to the type of surgery and the main complications recorded within 30 days postoperatively, performed at the National Cardiovascular Institute of Peru. Materials and methods. A descriptive study was conducted on all patients over 18 years of age who underwent cardiovascular surgery at the National Cardiovascular Institute “Carlos Alberto Peschiera Carrillo”. Results. During the year 2022, a total of 503 cardiac surgeries were performed. Of the patients undergoing surgery, 63.6% (320) were males. Isolated valvular surgery, primarily aortic or mitral valve replacement, was the most frequent surgical procedure, with 136 surgeries (27.0%). This was followed by myocardial revascularization surgery with 110 procedures (21.9%). Throughout the year, there were 23 deaths, resulting in an overall mortality rate of 4.5%. The mortality rate for elective surgeries was 2.8%, while for emergency surgeries, it was 14.3%. The most common complication was paroxysmal atrial fibrillation (14.0%), followed by surgical site infection with 52 cases (10.3%). Conclusions. Valvular surgery, whether isolated or combined with other procedures, was the most frequently performed. The obtained mortality rate is considered acceptable for a reference center.